Fostering Advocacy Behavior of Employees: A Corporate Social Responsibility Perspective From the Hospitality Sector - Ahmad, Naveed; Ullah, Zia; AlDhaen, Esra; Han, Heesup; Ariza-Montes, Antonio; Vega-Muñoz, Alejandro (Frontiers in Psychology, 2022)
Considering the stiff competitiveness situation in every sector, promoting the advocacy behavior of employees is of seminal importance for an organization. With this regard, the hospitality sector has no exceptions, however, a review of the prior literature uncovers that most of the prior studies on advocacy behavior were conducted from the standpoint of consumers, and the role of employees’ advocacy behavior, especially in the context of the hospitality sector, remained an understudied area. Research also shows that the corporate social responsibility (CSR) efforts of an organization can significantly influence employees’ behavior but the relationship of CSR to spur employees’ advocacy behavior was not discussed earlier. Against this knowledge gap, the current work aims to investigate the relationship between CSR and employees’ advocacy behavior in the hotel sector of a developing economy with the mediating effect of employees’ engagement. A hypothesized model was developed, which was validated by collecting data from different hotel employees through a self-administered questionnaire. The findings offer different theoretical and practical implications. Theoretically, one important implication was that the CSR perceptions of hotel employees can drive their advocacy behavior. Practically, the study implicates that hotels can improve their reputation significantly by converting their employees into advocates, as the personal information source is preferred over company-generated information sources. Moreover, the CSR commitment of a hotel can lead the employees to a higher level of engagement, which then motivates them to act as advocates.